A need-based, multi-level, cross-sectoral framework to explain variations in satisfaction of care needs among people living with dementia - Chiara De Poli (BMC Health Services Research, 2020)
Abstract Background Provision of care and support for people with dementia and family carers is complex, given variation in how dementia manifests, progresses and affects people, co-morbidities associated with ageing, as well as individual preferences, needs, and circumstances. The traditional service-led approach, where individual needs are assessed against current service provision, has been recognised as unfit to meet such complexity. As a result, people with dementia and family members often fail to receive adequate support, with needs remaining unmet. Current research lacks a conceptual framework for explaining variation in satisfaction of care needs. This work develops a conceptual framework mapped onto the care delivery process to explain variations in whether, when and why care needs of people with dementia are met and to expose individual-, service-, system-level factors that enable or hinder needs satisfaction. Methods Data collected through 24 in-depth interviews and two focus groups (10 participants) with people with dementia and family carers living in the North East of England (UK) were analysed thematically to develop a typology of care needs. The need most frequently reported for people with dementia (i.e. for support to go out and about) was analysed using themes stemming from the conceptual framework which combined candidacy and discrepancy theories. Results The operationalisation of the framework showed that satisfaction of the need to go out was first determined at the point of service access, affected by issues about navigation, adjudication, permeability, users’ resistance to offers, users’ appearance, and systems-level operating conditions, and, subsequently, at the point of service use, when factors related to service structure and care process determined (dis)satisfaction with service and, hence, further contributed to met or unmet need. Conclusion The conceptual framework pinpoints causes of variations in satisfaction of care needs which can be addressed when designing interventions and service improvements.